Subclinical hypothyroidism and digit span test performance in children: a systematic review and meta-analysis - Nadhea Debrinita Surya; Nicolas Daniel Widjanarko; Theressa Kristiayu Permatasari; Yuliana Yosephine; Ellen Wijaya (Paediatrica Indonesiana, 2022)
Background The digit span (DS) test is one of the most commonly used neuropsychological tests to assess certain cognitive domains, i.e., short-term verbal memory, working memory, and attention. Subclinical hypothyroidism (SH) may be associated with a risk of cognitive impairment in children and adolescents. Objective To evaluate the association between SH and DS test performance in children. Methods Eligible studies evaluating SH and DS test performance were included in this systematic review and further assessed for risk of bias using the Newcastle Ottawa Scale. We carried out a meta-analysis using the random effects model to determine mean difference with 95% confidence interval (95%CI) for continuous data. This systematic review was conducted according to the Preview Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) statement. Results Out of 1,511 participants in the five included studies, 129 had SH and 1,382 were euthyroid. The quality of all studies were fair to good. Three studies were extracted for meta-analysis, with results showing a trend toward a poorer DS test performance in the SH group compared to controls, although this difference was statistically insignificant (IV -0.57; 95%CI -1.61 to 0.46; P=0.28). There was no significant heterogeneity among the included studies (I2=0%; P=0.69). Conclusion No significant association was noted between SH and the domains of cognitive function assessed using the DS test. Several intrinsic and extrinsic factors and inability of the DS test to detect subtle impairment may limit its usefulness in children.